Microencapsulation of Moringa oleifera L. extract in liposomes: Evaluation of antioxidant and antiglycation activities, cytotoxicity and skin biometric parameters - Gimenis, Janine Mailho [UNESP]; Figueiredo, Célia Cristina Malaguti [UNESP]; Gomes, Amanda da Costa [UNESP]; Granero, Filipe Oliveira [UNESP]; Ximenes, Valdecir Farias [UNESP]; Silva, Luciana Pereira; Bronzel Junior, João Luiz [UNESP]; Leite e Silva, Vânia Rodrigues; Silva, Regildo Márcio Gonçalves da [UNESP] (Elsevier, 2023)
Moringa oleifera L. has demonstrated its beneficial effects on environment, nutrition and health, and it has been widely used as an important food supplement for human health due to the presence of antioxidant compounds that can act to prevent several diseases associated to oxidative stress and protein glycation. The search of new technologies has highlighted liposomes as carrier system that offers advantages such as biocompatibility, bioavailability and low toxicity. M. oleifera hydroethanolic extract (MoHE) and liposomes (empty (EmL) and extract-loaded (ExL)) were prepared for the analyses. High Performance Liquid Chromatography-Diode array detector-Mass Spectrometer (HPLC-DAD-MS) was performed to identify phytochemicals of MoHE. Scanning electron microscopy (SEM), polydispersity index (PDI) zeta potential and dynamic light scattering (DLS) were performed to characterize the vesicles. Thermal stability and TBARS method were performed to determine the stability of liposomes. Antioxidant activity was determined by DPPH radical scavenging and oxygen radical absorption capacity (ORAC-FL). Antiglycation activity was evaluated by determination of free amino groups and inhibition of AGEs formation. Cytotoxicity was evaluated by MTT assay and skin biometric parameters were evaluated in vivo. It was observed the presence of quercetin and kaempferol glycosides and chlorogenic acid derivatives. SEM showed the formation of liposomes and characterization demonstrated that ExL presented a low mean size and PDI, indicating homogeneity. Besides, liposomes showed thermal stability. Antioxidant evaluation by DPPH showed 85.84% (MoHE at 5 mg mL−1) and 69.98% (ExL at 10 mg mL−1) antioxidant activity and both samples presented antioxidant activity in ORAC assay. MoHE and ExL presented the highest free amino groups and inhibition on AGEs formation. MoHE did not present cytotoxicity and base with MoHE (BMoHE) showed the greatest mean skin hydration; however, base with ExL (BExL) presented the lowest transepidermal water loss. Therefore, M. oleifera presents potential to be used as a source of natural compounds that can be encapsulated in liposomes for the application in new formulations for cosmetical and pharmaceutical industries.
Keywords: Food supplement; Functional food; Microencapsulation; Oxidative stress; Skin care